"Як научить байдужих відчувати? Як розбудити розум, що заснув?" - Єрмоленко, С. (Культура слова, 2020)
У статті розглянуто особливості мовомислення Лесі Українки
на прикладі аналізу характерного словника, поетичної фразеології
і синтаксично-інтонаційних структур. Семантику ключових для
мовотворчості поетеси слів проаналізовано з проєкцією на текстові
трансформації. Зафіксовані словесно-образні асоціації поетеси
засвідчують взаємодію думки (розуму) і почуттів у вербалізації
мовної картини світу. Наголошено на антитетичному мисленні як
джерелі формування мовно-естетичних знаків української культури.
Увиразнено символіку СЛОВА як інструмента поетичної творчості,
наділеного почуттєвим змістом. Modern receptive poetics encourages the study of verbalized end-toend
motives of Lesia Ukrainka’s work. Embodied in various linguistic
forms – lexical-semantic, phrase-forming, syntactic-rhythmic and
intonation, Lesia Ukrainka’s poetic texts testify to the change of the
traditional dictionary of Ukrainian poetry, filling it with new associative
connections, consistent with the needs of a particular historical era.
Emphasis is placed on the connection of the word with music, not
only formal, but also concretized in rhythms, syntactic and intonational
variation of verse lines. The considered textual variants of the sonnet
“Fantasy” convince in dynamism, originality of figurative-associative
linguistic thinking of the poetess. The dynamics is traced in the textual
representation of concepts фантазія, мрія, сон життя, in the symbolic
meaning of the token камінь and вогонь, камінь and байдужість.
Emphasis is placed on various forms of contrast expression – from
antonyms, oxymorons, to opposing sentences-judgments. They are
representatives of the logical and sensual content of Lesya Ukrainka’s
poetic texts. On the example of evaluative significant words to the concepttoken
WORD as an instrument of poetic creativity, a conclusion about the
antithetical thinking of the poetess is made.
The dynamic perception of semantics is fixed вогонь, жар, пожежа,
associated with a negative assessment of the destructive element, but in
the poetic contexts of the author, these symbols are positively assessed
as the ability to be a stimulus to creative inspiration, inflammatory,
caring soul of the creator. Poetic phraseology to denote the concept of
“indifference”, which acquires the meaning of linguistic and aesthetic sign
in the Ukrainian language culture, is recorded.